Hybrid contact lenses for the correction of primary and induced ametropias - V. V. Neroev; A. V. Myagkov; O. V. Guryanova; A. T. Khandzhyan; A. I. Yakunina (Российский офтальмологический журнал, 2020)
The review presents the data on the use of hybrid contact lenses (HCL), a modern method of contact correction of ametropias of diverse origins. A HCL has a central rigid optical zone made of highly gas-permeable material and a flexible peripheral part made of hydrophilic material. These lenses combine the optical effect of gas-permeable corneal lens with the comfort and stable fitting of soft contact lenses. Compared with the corneal (RGP) lenses, HCLs are more comfortable, often are better centrated and more stably fit on the eye. HCLs are successfully used in various refractive disorders: ametropias (with regular cornea), irregular astigmatism, presbyopia, including that combined with astigmatism. This type of lens is a good option of contact correction for patients who have high requirements to the quality of vision.